MENUJU DUNIA KERJA DENGAN BUDAYA KERJA DI INDUSTRI PARIWISATA KOTA PADANG - Mukti Diapepin (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The work culture is an indicator that determines success in managing the tourism industry in the city of Padang. The success of Padang City Tourism rose from the post-earthquake deterioration in 2009, becoming one of the references for job seekers to use the momentum to find, or open business opportunities. This research is descriptive, carried out to get a description or description of work culture for job seekers. Then an analysis of the development of tourism objects is carried out with skill readiness from beginners. The work culture is absolutely understood by every job seeker. Given, the elements and indicators that exist in the work culture, have a large output in the tourism industry